Intraoperative Use of Robotics With Navigation for Pedicle Screw Placement in Treatment of Pediatric High-grade Spondylolisthesis: A Preliminary Report. Issue 10 (9th November 2021) - Linden, Gabriel S.; Birch, Craig M.; Hresko, M. Timothy; Cook, Danielle; Hedequist, Daniel J.
Abstract : Background: Accurate pedicle screw placement is critical to surgically correct pediatric high-grade spondylolisthesis (HGS). The recent advent of robotics coupled with computer-assisted navigation (RAN) may represent a novel option to improve surgical outcomes of HGS, secondary to enhanced pedicle screw placement safety. This series presents the HGS-RAN technique adopted by our site, describing its surgical outcomes and feasibility. Methods: Consecutive patients with a diagnosis of HGS (Meyerding grade III to V), operated on using RAN from 2019 to 2020 at a single-center were reviewed. Demographics, screw accuracy, sagittal L5-S1 parameters, complications, and perioperative outcomes were described. All patients were treated with instrumentation, decompression, posterior lumbar interbody fusion, and reduction. Robotic time included anatomic registration to end of screw placement. Screw accuracy—defined as a screw placed safely within the planned intrapedicular trajectory—was characterized by the Gertzbein-Robbins system for patients with additional 3-dimensional imaging. Results: Ten HGS patients, with an average age of 13.7 years old, were included in the series. All 62 screws were placed without neurological deficit or complication. Seven patients had additional 3-dimensional imaging to assess screw accuracy (42 of 62 screws). One hundred percent of screws were placed safely with no pedicle breaches (Gertzbein-Robbins—grade A). Thirty screws (48%) were placed through separate incisions that were percutaneous/transmuscular and 32 screws (52%) were inserted through the main incision. There were statistically significant improvements in L5 slippage ( P =0.002) and lumbosacral angle ( P =0.002), reflecting successful HGS correction. The total median operative time was 324 minutes with the robotic usage time consuming a median of 72 minutes. Median estimated blood loss was 150 mL, and length-of-stay was a median 3 days. Conclusions: This case-series demonstrates that RAN represents a viable option for HGS repair, indicated by high screw placement accuracy, safety, and L5-S1 slippage correction. Surgeons looking to adopt an emerging technique to enhance safety and correction of pediatric HGS should consider the RAN platform. Level of Evidence: Level IV—therapeutic study.